Recent advances in Polygonaceae endophytes: diversity, secondary metabolites and biotechnological applications - Chen, Zhi-Min; Tang, Rui-Qi (Frontiers in Bioengineering and Biotechnology, 2025)
The Polygonaceae family comprises numerous traditional Chinese medicinal herbs and serves as a significant source of natural products with bioactive properties. Endophytes, which colonize the internal tissues of plants, have various beneficial effects on their hosts. The diverse communities of endophytes within Polygonaceae plants can promote host growth and enhance stress resistance by producing plant hormones and improving the metabolic levels of host cells. Additionally, endophytes can induce the accumulation of secondary metabolites in host plants. Furthermore, endophytes possess the capability to produce a variety of bioactive compounds, which can be further utilized in the biosynthesis of natural pharmaceuticals. Although research on endophytes of Polygonaceae plants has made notable progress, it has been rarely reviewed comprehensively. This review focuses on the diversity of endophytes and their effects on host plants in four representative genera of Chinese medicinal Polygonaceae: Reynoutria, Fagopyrum, Rheum, and Rumex. We also discuss the application of bioactive metabolites produced by these endophytes and summarize recent advances in their biosynthesis in microbial cell factories. The review aims to provide insights into the identification and application of endophytic microbial resources from Polygonaceae plants.